Wastewater-based epidemiology to assess the occurrence of new psychoactive substances and alcohol consumption in Slovakia - Brandeburová, Paula; Bodík, Igor; Horáková, Ivana; Žabka, Dušan; Castiglioni, Sara; Salgueiro-González, Noelia; Zuccato, Ettore; Špalková, Viera; Mackuľak, Tomáš (Ecotoxicology and environmental safety, 2020)
Consumption of alcohol and new psychoactive substances (NPS) in a population or during special events (music festivals) is usually monitored through individual questionnaires, forensic and toxicological data, and drug seizures. However, consumption estimates have some biases due mostly to the unknown composition of drug pills for NPS and stockpiling for alcohol. The aim of this study was to evaluate for the first time the real use of alcohol and the occurrence of NPS in Slovakia by wastewater-based epidemiology (WBE). Urban wastewater samples were collected from nine Slovak cities over two years (2017-2018) and during three music festivals. The study included about 20% of the Slovak population and 50 000 festival attendees. The urinary alcohol biomarker ethyl sulfate (EtS) and thirty NPS were analyzed by liquid chromatography tandem mass spectrometry (LC - MS/MS). EtS concentrations were used for estimating the per capita alcohol consumption in each city. The average alcohol consumption in the selected cities and festivals in 2017-2018 ranged between 7 and 126 L/day/1000 inhabitants and increased during the weekends and music festivals. Five NPS belonging to the classes of synthetic cathinones (mephedrone, methcathinone, buphedrone and pentedrone) and phenethylamines (25-iP-NBoMe) were found in the low ng/L range. Methcathinone was the most frequently detected NPS, while the highest normalized mass load corresponded to mephedrone (3.1 mg/day/1000 inhabitants). Wastewater-based epidemiology can provide timely information on alcohol consumption and NPS occurrence at the community level that is complementary to epidemiology-based monitoring techniques (e.g. population surveys, police seizures, sales statistics).
Keywords: Chromatography, Liquid; Humans; Festivals; Tandem Mass Spectrometry; estery kyseliny sírové; Psychotropic Drugs; Alcohol Drinking; dovolená; pití alkoholu; psychotropní léky; Urban wastewater; ethanol; epidemiologie odpadních vod; lidé; Slovakia; Slovenská republika; Wastewater; tandemová hmotnostní spektrometrie; Cities; Waste Water; chromatografie kapalinová; Holidays; New psychoactive substances; Alcohol; Sulfuric Acid Esters; odpadní voda; Ethanol; Wastewater-Based Epidemiological Monitoring; velkoměsta; Liquid chromatography-tandem mass spectrometry